Plasma levels of 7-hydroxylated dehydroepiandrosterone (DHEA) metabolites and selected amino-thiols as discriminatory tools of Alzheimer's disease and vascular dementia - Bicíková, Marie; Rípová, Daniela; Hill, Martin; Jirák, Roman; Havlíková, Helena; Tallová, Jaroslava; Hampl, Richard (Clinical chemistry and laboratory medicine, 2004)
OBJECTIVE: The early differential diagnosis of Alzheimer's disease (AD) remains still problematic. We developed a laboratory test enabling us to distinguish patients with AD from those with vascular dementia (VD) and healthy subjects. METHODS: The AD group consisted of 22 women and 18 men. The VD group consisted of 16 women and 8 men. Age-matched controls consisted of 12 women and 9 men. Plasma pregnenolone sulfate (PregS), dehydroepiandrosterone (DHEA) and its sulfate (DHEAS) were determined by radioimmunoassay. 17-Hydroxypregnenolone (17Preg) and 7-hydroxylated metabolites of DHEA (7alphaDHEA, 7betaDHEA) were determined by radioimmunoassay after separation by high performance liquid chromatography (HPLC). Homocysteine (Hcy), cysteine (Cys), cysteinylglycine (Cysgly) and glutathione (GSH) were measured by HPLC. RESULTS: The ANOVA results of significant between-group differences were as follows: The PregS and the 17-Preg and DHEAS levels were independent from the diagnosis. The 7alphaDHEA levels significantly depended on the sex (p < 0.05) and diagnosis (p < 0.01). Amino-thiols were influenced by the diagnosis (p < 0.01, p = 0.0541, p < 0.01 and p = 0.0536 for Cys, Hcy, Cysgly and GSH, respectively). Using a stepwise backward regression analysis, the following parameters were obtained: X = 11.5 + 4.03 x sex +1.09 x Hcy + 0.190 x PregS - 4.76 x DHEAS + 3.00 x DHEA - 34.3 x 77alphaDHEA - 0.885 x Cysgly from which P-value as a discriminator was calculated according to the formula: P = 1/(1 + e(-x)). Then, for P > 0.5, a subject was considered as AD-positive (with 89% correct prediction). DISCUSSION: The opportunity of early differential diagnosis of AD should help physicians to use suitable treatment for retardation of pathological processes.
Keywords: radioimunoanalýza; senioři; pregnenolon; Cysteine; Radioimmunoassay; senioři nad 80 let; dipeptidy; Dehydroepiandrosterone Sulfate; Statistics, Nonparametric; Dehydroepiandrosterone; Glutathione; Predictive Value of Tests; sexuální faktory; homocystein; Middle Aged; Sensitivity and Specificity; mužské pohlaví; prediktivní hodnota testů; Chromatography, High Pressure Liquid; Dipeptides; Alzheimer Disease; cystein; dehydroepiandrosteronsulfát; neparametrická statistika; Homocysteine; vysokoúčinná kapalinová chromatografie; Aged, 80 and over; logistické modely; 17-alfa-hydroxypregnenolon; ženské pohlaví; 17-alpha-Hydroxypregnenolone; Dementia, Vascular; Humans; glutathion; Sex Factors; biologické markery; sulfhydrylové sloučeniny; lidé středního věku; vaskulární demence; senzitivita a specificita; Logistic Models; Pregnenolone; Alzheimerova nemoc; dehydroepiandrosteron; Biomarkers; Female; Aged; Sulfhydryl Compounds; lidé; Male